Influential Article Review - Entrepreneurial Endeavors In An Open National Innovation System (ONIS) - Watkins, Roderick; Lawson, Gayle (Journal of Strategic Innovation and Sustainability, 2019)
This paper examines entrepreneurship and innovation. We present insights from a highly influential paper. Here are the highlights from this paper: In the context of globalization, international processes do affect the national innovation system (NIS), increasing the relationship between its agents and its components within and with external agents. The paper seeks to determine the openness and internationalization processes in the internal features of Mexico’s NIS and estimate its impacts. This information could allow for a better use of scientific, technological, and innovation—internal and external—capabilities. The point of departure is the concept of innovation, which was developed for the industrial revolution where products and technological processes are emphasized, with a scope of radical to incremental innovation, as a function of the level of their impacts. Implicitly, innovation has been conceptualized internally within the company, i.e., closed innovation, especially in large companies with research and development departments. However, companies have undertaken various forms of collaboration to reduce costs particularly for R&D, which fall within the concept of open innovation. Based on the concept of open innovation, an open national innovation system (ONIS) has been proposed with internal and external components and relationships.This paper argues that the openness of innovation needs to be applied both at firm level and through a NIS as a way of handling the risks involved in innovation better. Thus, firms’ open innovation must correspond to an ONIS, matching the openness and internationalization of its knowledge components and agents: firms and universities supported through government policies. The empirical analysis is exploratory, based on a direct and indirect source to assess how highly developed the Mexican ONIS is to propose some policies. For our overseas readers, we then present the insights from this paper in Spanish, French, Portuguese, and German.